S2 The impact of pulmonary rehabilitation (pr) completion and outcome on subsequent hospital admissions in patients with copd. results from the national copd audit. (15th November 2017) - Steiner, MC; Holzhauer-Barrie, J; Lowe, D; McMillan, V; Loo, V van; Roberts, CM
Abstract : Introduction: Clinical trials suggest attendance at PR reduces subsequent hospitalisation rates. However, whether this benefit occurs in routine clinical practice is uncertain. We analysed admission rates and days spent in hospital 90 and 180 days after assessment for PR in the 2015 national PR audit cohort. Methods: PR services across England and Wales provided data for all consenting patients assessed for PR between Jan and April 2015. Cumulative rates of admission to hospital and numbers of days spent in hospital at each timepoint (and between the 90 and 180 day timepoints) were extracted from Hospital Episode Statistics (HES) and compared between patients who did and did not complete PR and between those reaching and not reaching accepted thresholds for clinically important improvements (MCIDs) in exercise and health status measures. Results: Data for 7135 patients included in the audit in England were extracted. Overall admission rates (proportion with at least one admission) were18.6% and 29.6% at 90 and 180 days respectively. At each timepoint, completion of PR (defined by there being a discharge assessment) was associated with a reduced risk of admission to hospital (compared with non-completion) (90 days: 13.1 vs 26.4%; 180 days: 23.7 vs 37.9%; 91–180 days: 15.0 vs 21.7%; all p<0.001) and reduced days spent in hospital (90 days: Mean 3.1 vs 7.1 days; 180 days: mean 4.8 vs 9.4 days; 91–180 days: 4.91 vs 7.6 days; all p<0.001). Reaching the MCID for exercise measures after completion of PR was associated with reduced risk of admission at 180 days (and 91–180 days) (p<0.05) but not reduced days spent in hospital. Changes in health status measures were not associated with admission rates or days spent in hospital. Conclusion: Successful completion of PR is associated with reduced risk of hospitalisation and reduced days in hospital up to 180 days after assessment. Although some of this effect may be due to case-mix variation, actions to enhance uptake and completion rates for PR may be effective measures to reduce health care resource utilisation for patients with COPD.